Il contributo di A. Rimoldi alla Storia religiosa della Lombardia - Vaccaro, Luciano (La Scuola Cattolica, 2025)
In the editorial initiative of the «Religious history of the Lombardia» the role of mgr. Rimoldi, as shows the reconstruction offered by these pages, is the result of the utmost importance from the beginning, when he supported the project designed by mgr. Carlo Colombo. Later, in order to carry out the project, mgr. Rimoldi played a role that the author of this contribution considers vital enough to describe it as a director «in every effect».